PRAGMA-DIALECTICAL STRATEGIES OF MANOEUVRING IN POLITICAL ARGUMENTATION: A REVIEW OF LITERATURE - Salman, Hawraa Talib; Yusoff, Zailin Shah Binti (International Journal of Psychosocial Rehabilitation, 2020)
A review paper commonly creates an understanding of a given topic for the reader through discussing the findings introduced in the latest research paper. Hence, it can be regarded as a text that contains a summary of the scholarly research on certain topics. Reviews are important in that they enable the reader to have an idea about the published works in a given field of study without reading the entire documents or public books. According to Jesson and Lacey (2017), reviews are classified into three categories; narrative or traditional, scoping, and systematic quantitative review. To Khan (2017), the main purpose of a narrative review is to give the reader a comprehensive overview of the topic to highlight important areas of research and define research questions. Whereas the principle purpose of scoping review is to find all the materials on the topic, “When undertaking a scoping review, it is important to systematize your search strategies to ensure you can replicate your searches and to attend to any gaps that appear in results” (Sandle, 2016:73). A systematic review, on the other hand, attempts to collect secondary data and synthesize findings qualitatively or quantitatively (Boland & Dickson 2017). The current review is intended to be a narrative one. It aims to summarize and describe the literature published on the topic of ‘strategic manoeuvring and its strategies’ in relation to political argument. In response to achieve the mentioned aims, this review posits that politicians be inclined to use certain manoeuvring strategies more than others in in political speeches and interviews.The papers discussed here are chosen from peer-reviewed journals documented under Google Scholar, published in the last 13 years; 2006-2018 using many search keywords like ‘pragma-dialectics’, ‘pragmatics’, ‘speech acts’, ‘strategic manoeuvring’, and ‘political argumentation’. The speech act literature is grouped according to the type of argumentation on the basis of topic relatedness first and the type of perspective involved. So, the papers with similar topics sharing the same argumentative discourse are reviewed together. In addition, the studies discussed are only those on political manoeuvring since the scope of this paper is limited to political argumentative studies. the study highlights that the use of strategic manoeuvring in political argumentation is widespread. It also clarifies certain difficulties in evaluating the nature of manoeuvring whether it is a social, pragmatic or psychological phenomenon. Each discourse has its ideology. Each argumentative political study has its frame.This paper reviews the literature related to strategic manoeuvring as used in political argumentation. It aims to present the findings and discussions of the previous studies which call for further research. To look at more recent content, the literature search comprised in this review covered current research papers published between 2004 to 2018. A substantial number of scholarly articles were identified andexamined based on keywords search in Google Scholar. The discussions and findings are classified according to topic relatedness and the type of argumentation.